2021
DOI: 10.3390/metabo11110779
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Consuming White Button Mushroom Agaricus bisporus on the Brain and Liver Metabolome Using a Targeted Metabolomic Analysis

Abstract: A targeted metabolomic analysis was performed on tissues derived from pigs fed diets supplemented with white button mushrooms (WBM) to determine the effect on the liver and brain metabolome. Thirty-one pigs were fed a grower diet alone or supplemented with either three or six servings of freeze-dried WBM for six weeks. Tissue metabolomes were analyzed using targeted liquid chromatography-mass spectrometry (LC-MS) combined with chemical similarity enrichment analysis (ChemRICH) and correlated to WBM-induced cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Studies also found that morels exhibit anti-inflammatory and free radical scavenging effects ( 33 ), as well as hepatoprotective activity ( 34 ). Although research has be conducted on other mushrooms and their extracts can have a health impact on the host by improving the gut microbiota, such as Agaricus bisporus ( 35 ), Pleurotus eryngii ( 36 ), Auricularia auricular ( 28 ), Antrodia cinnamomea ( 37 ), and Ganoderma lucidum ( 38 ), limited studies have reported on how morels modulate the gut microbial composition and promote health ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also found that morels exhibit anti-inflammatory and free radical scavenging effects ( 33 ), as well as hepatoprotective activity ( 34 ). Although research has be conducted on other mushrooms and their extracts can have a health impact on the host by improving the gut microbiota, such as Agaricus bisporus ( 35 ), Pleurotus eryngii ( 36 ), Auricularia auricular ( 28 ), Antrodia cinnamomea ( 37 ), and Ganoderma lucidum ( 38 ), limited studies have reported on how morels modulate the gut microbial composition and promote health ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conditions like AD and dementia significantly challenge healthcare systems worldwide, prompting the need for new prevention and treatment methods [ 122 ]. NDs are also associated with early-stage gastrointestinal issues, such as constipation and delayed gastric emptying, alongside an imbalance in intestinal flora [ 123 ].…”
Section: Functional Fungal Polysaccharides and The Gut–brain Connecti...mentioning
confidence: 99%